Bilateral dorsal foot pain in a young tennis player managed by neurodynamic treatment techniques - Nelson, R.; Hall, Toby (2011)
Exercise-related lower limb pain represents one of the most common presentations in sports medicine practice. This is usually caused by musculoskeletal overuse injuries but not uncommonly, a neuropathic cause may be suspected. A review of the literature revealed that peripheral neuropathic pain has never been documented in a child. It is possible that peripheral neuropathic pain of spinal origin may be more prevalent in children than previously recognized. This case report describes the presentation of a 12 year old tennis player with bilateral dorsal foot pain, who presented with positive findings of peripheral nerve sensitization which was successfully managed using neurodynamic treatment techniques. Differential diagnoses are considered and treatment and management described. A discussion of the clinical reasoning which led to the patient’s diagnosis is included. This case report suggests the effectiveness of neurodynamic treatment in a child with bilateral foot pain who fulfilled published criteria for peripheral nerve sensitization. However, the single case methodology employed in this study limits generalization of its findings. Further studies are warranted to investigate the role of neurodynamics in musculoskeletal pain disorders in children.